Unilateral absence of internal carotid artery: A rare case report - Das, Uddalok; Selim, Sahajada; Singh, Ramudar; Pandit, Narayan (Indian Journal of Case Reports, 2021)
Unilateral absence of internal carotid artery (ICA) is a rare congenital anomaly. We present the case of a 35-year-old man with episodes of recurrent strokes in the past and now presenting with right-sided upper limb weakness. Radiological diagnostic workup revealed a thin left ICA in the neck with non-visualization beyond petrous bone in the intracranial course. The ipsilateral brain parenchyma is supplied by vessels from the contralateral side of the Circle of Willis. As the patient had no evidence of a cerebrovascular accident on radiological evaluation and no neurological signs and symptoms, he was discharged with anticoagulant medications with the advice of follow-up. This is the first report to describe a case of ICA agenesis with a pattern of collateral circulation that doesn’t fit any of the six types described by Lie.